Development of Mathematics Learning Media Using Wordwall to Improve Students' Interest and Learning Outcomes - Putra Mei Anugrah Halawa; Yakin Niat Telaumbanua; Ratna Natalia Mendrofa; Sadiana Lase (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study addresses the limited use of technology-based instructional media and insufficient instructional time in mathematics learning. It aims to develop and evaluate Wordwall-based learning media in terms of validity, practicality, and effectiveness in improving students’ learning interest and achievement. The study employed a Research and Development design using the ADDIE model up to the evaluation stage. Participants included 32 eighth-grade students from SMP Negeri 3 Huruna and one mathematics teacher. Data were collected through expert validation involving three validators, student and teacher response questionnaires, and learning achievement tests. Data analysis combined descriptive qualitative analysis with quantitative analysis using percentage scores and pretest–posttest comparisons. The findings indicate that the developed media is valid in terms of content, language, and visual design; highly practical, as reflected by positive responses from more than 90 percent of students and teachers; and effective in improving learning interest, with an average increase of 25 percent, as well as learning outcomes, with an N-gain of 0.62 in the medium–high category. The novelty of this study lies in positioning Wordwall not merely as a gamification tool, but as an interactive learning medium systematically integrated within the ADDIE instructional design framework for mathematics learning. Theoretically, this study strengthens evidence on the role of gamification within instructional design. Practically, it offers teachers a viable strategy to address time constraints while enhancing student engagement and learning outcomes.